Activity and expression of different members of the caspase family in the rat corpus luteum during pregnancy and postpartum - Peluffo, Marina Cinthia (2007)
Studies were designed to examine the expression and activity of four caspases that contribute to the initial (caspases-2, -8, and -9) and final (caspase-3) events in apoptosis in the rat corpus luteum (CL) during pregnancy (days 7, 17, 19, and 21 of gestation), postpartum (days 1 and 4), and after injection (0, 8, 16, 24, and 36 h) of the physiological luteolysin PGF2α. In addition, the temporal relationship of caspase expression/activity relative to steroid production and luteal regression was evaluated. During pregnancy, the activity of all four caspases was significantly greater on day 19, before a decline in CL progesterone (P) and CYP11A1 levels at day 21 of gestation. The levels of the caspase-3 active fragment (p17, measured by Western blot) also increased at days 19 and 21 of pregnancy. Immunohistochemical analyses detected specific staining for the caspases in luteal cells (large and small) as well as in endothelial cells. However, the percentage of apoptotic cells did not increase in the CL until postpartum. Following PGF2α injection, there was a significant decrease in CL P by 24 h, although the activity of all four caspases did not increase until 36 h posttreatment. The active p17 fragment of caspase-3 also significantly increased at 36 h post-PGF2α. These results suggest that an increase in the activity of caspases-2, -8, -9, and -3 is associated with the early events of natural luteolysis at the end of pregnancy. Also, the exogenous administration of the luteolysin PGF2α may regulate members of the caspase family.